UHT milk machine / Muhammad Hilmi Shairazi Mustafa...[et al.] - Shairazi Mustafa, Muhammad Hilmi; Zakaria, Nabil Aiman; Mazlan, Rini Farahana; Mohd Hussain, Nur Farahana (2018)
Cosmofarm Enterprise is a small medium company that facing some problem regarding goat's milk processing machine. The problem effects the time taken for each production, where it will longer the production time and it will become inefficient for the production of each product. The current pasteurize machine at the company lack of ability to produce Ultra High Temperature (UHT) milk where it causes the milk to quickly get spoiled. The different between UHT and pasteurize milk is the period of the spoiled, which UHT milk can be good up to 6 months but pasteurize milk can be spoiled just between 2 to 3 weeks. The pasteurize machine that proposed will have an ability to produce UHT milk where this machine can boil up the milk at UHT production temperature, 135°C. The pasteurize machine is not proposed as a single idea, but the idea is to connect all the machine to produce a high quality UHT milk in term of hygiene and variety of flavor. Thus, the current machine that already able at Cosmofarm will be upgrade and few machines will be add and connected by stainless steel pipe. Then, it will work continuously, and unfortunately will lighteryfhe workers burden. This product was only targeted to Cosmofarm as we only focused to their problem of goat's milk production. The cost that will covered up the whole upgraded product is RM 90,000.00 approximately. The cost was calculated by involved the cost of the improvement and the addition of few machines that were economically chose and also compared to other cost of machines that available in the market. The management team included the financial team, operational team, marketing team and administration team. Each team will conduct different task that suitable as their position. All the tasks will help in developing the product that will improve goat's milk production at Cosmofarm Enterprise.